Visualisasi Efek Daun Dalam Mikroskop Melalui Teknik Slip Trailing - Nursyafiqa, Binti Mamat Hanafiah (Universiti Malaysia Sarawak(UNIMAS), 2018)
This scientific writing study is aimed at documenting the studies that have been done on trailing slip technique in the form of abstracts that are processed through leaf cuts that are viewed using a microscope. This study will explain how to explore the use of slips in the production of contemporary ceramics. Researchers will also study and try to understand how appropriate production and effects are applied to the production of ceramics using the technique of trailing slip carefully so that it becomes hard and avoids filling. Effective application will influence the effectiveness and creativity of an end result so that the applied techniques will be a work that will attract the attention of the audience. Additionally, the theories taken with regard to the techniques used to apply will be further and thoroughly explained regarding the study problem. Through research conducted by researcher can know more about how to apply trailing technique in contemporary ceramics. The production of ceramics in contemporary art is based on the expertise and creativity of a work. But at the end of the study the researcher emphasized how technology can help to produce the work to be more appealing by having the value and meaning in the work.